2018
DOI: 10.5897/jpbcs2018.0726
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat stress on common bean under natural growing conditions in three locations in different climate zones in the state of So Paulo, Brazil

Abstract: Common bean (Phaseolus vulgaris L.) originated in medium to high altitude regions and is sensitive to high temperatures. Climate changes from an increase in global temperatures are foreseen, and therefore better understanding of the mechanisms of heat tolerance is necessary. In this context, the aim of this study was to investigate the effects of heat stress on twelve common bean genotypes under natural growing conditions in three locations (Campinas, Votuporanga, and Ribeirão Preto, SP, Brazil) and in two gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
3
1
0
Order By: Relevance
“…Due to more heat stress pressure in the greenhouse when compared to the rainfed field, yield was zero for almost all genotypes, except for genotypes G191, G183, G123, G13, G50, G59, G192, G96, and G181 with scores between 1.0 and 3.0. These results are in agreement with those of da Silva, dos Reis [66]. P. acutifolius was more resistant to heat stress among bean genotypes despite late flowering.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Due to more heat stress pressure in the greenhouse when compared to the rainfed field, yield was zero for almost all genotypes, except for genotypes G191, G183, G123, G13, G50, G59, G192, G96, and G181 with scores between 1.0 and 3.0. These results are in agreement with those of da Silva, dos Reis [66]. P. acutifolius was more resistant to heat stress among bean genotypes despite late flowering.…”
Section: Discussionsupporting
confidence: 92%
“…This is easy to understand because, due to heat stress in the greenhouse, yields were zero for almost all genotypes. These results are in agreement with those of Porch [21], da Silva, dos Reis [66] which showed that the 100-seed weight, the number of pods per plant, and the harvest index were agronomic factors that could better influence the yield when the plant is subjected to heat stress. P. coccineus species with intermediate genotypes performed better in the field.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In another important horticultural crop, the heat-sensitive common bean (Phaseolus vulgaris L.), genome-environment associations revealed 22 genes related to biological processes involved in the heat stress response, such as the activation of HSPs, abiotic stress signalling, germination and seedling development, flowering time, protein thermo-stability, molecular chaperones, and cell-wall integrity [129]. Nevertheless, to date, stress priming studies in the common bean have mainly focused on the morphophysiological effects of heat stress [177] and the development of preliminary epigenomic maps linked to important agronomic traits [178,179]; hence, to what extent such epigenetic changes are inter-/or transgenerationally inherited in the common bean is still a largely unexplored field.…”
Section: Heat Stressmentioning
confidence: 99%